Methodical solutions for improving the effectiveness of studying mathematical disciplines by students of cyber security and computer sciences - Zhylenko, T.; Martynova, N.; Kotuch, E. (New Collegium, 2023)
The paper considers the influence of graphic methods of summarizing on the effectiveness of teaching mathematical disciplines. Emphasis is placed on the works of modern specialists in this field. The main points of traditional note-taking, its style, form, structure are analyzed, as well as the shortcomings and influence on the perception and assimilation of the material. The essence of various methods of modern graphic note-taking: scribing and sketch noting, their main components, which influence the improvement of memorization of new information, are revealed. Examples of the introduction of graphic note-taking in the course of mathematics during the study of elements of linear algebra and analytical geometry, namely: curves and surfaces in space, material on the theory of matrices and determinants, systems of linear algebraic equations, its effectiveness in the perception and assimilation of the material, are demonstrated. The given examples clearly show the difference between scribing and sketchouting. A fragment of the survey of students majoring in cyber security and computer science was demonstrated. Its analysis was carried out and positive and negative responses were presented both graphically and in percentages, survey questions were given. A conclusion was made regarding the importance of implementing modern note-taking methods in the study of mathematical disciplines. The opinion of modern participants in the educational process is considered when planning the educational trajectory in the future.